Effectiveness of A Training Program Based on Differentiation Instruction Theory in Academic Achievement, among ninth Grade Students in biology Course - Al- Shaweesh, Juman Ghalib (Journal of Educational and Psychological Sciences, 2021)
The study sought to identify the effect of using differentiated instruction in the achievement of biology among ninth grade students. population of this study (25) students was chosen for the control group and (25) students for the experimental group. During the first semester of (2021/2020). to achieve the objectives of this study, a biology achievement test was prepared. results showed that there were a statistically significant differences on achievement test in favor of the grades of the experimental group. this study recommended hiring differentiated teaching because of its effect on students’achievement.
Keywords: differentiated teaching; biology; achievement